INFLUENCE OF GRINDING ON THE STRUCTURE AND COLOUR PROPERTIES OF TALC, BENTONITE AND CALCITE WHITE FILLERS - Christidis G.E.; Makri P.; Perdikatsis V. (My University, 2004)
The influence of grinding on colour and particle-size properties of talc and smectite from a white bentonite were studied and compared with a fine-grained calcite from a chalk. Grinding decreased the grain size of all three minerals. The crystallite size and structure of smectite was not affected but the crystallite size of talc decreased. The Si-O-Mg and Mg-O bonds of talc were disrupted and cation exchange capacity increased with increasing grinding. Delamination of talc crystallites was observed in the initial stages of grinding, whereas with more intense treatment, amorphous material was formed. Comminution improved the colour properties of all three minerals, namely brightness, L *(lightness) and E*ab (deviation from perfect white diffuser). Grinding time exerts greater influence on the reflectance from calcite surfaces than from clay minerals. This difference is attributed to continuous formation of progressively smaller diffuse reflection units forming a smoother calcite surface. Decrease of grain size does not form considerably smaller diffuse reflection units in clay minerals unless delamination takes place. With prolonged grinding, amorphization forms additional diffuse reflection units and a smoother surface due to comminution.
Keywords: talc; bentonite; calcite; grinding; crystallite size; diffuse reflection unit